Tanshinone IIA Accomplished Protection against Radiation-Induced Cardiomyocyte Injury by Regulating the p38/p53 Pathway - Gang Wang; Li Ma; Bowen Wang; Fentang Gao; Jianfeng Li; Hongyi Cai; Juan Wang; Tiancheng Zhang; Hao Guo; Ping Xie; Yi Li (Mediators of Inflammation)
Background. Radiotherapy is one of the major strategies for treating tumors, and it inevitably causes damage to relevant tissues and organs during treatment. Radiation-induced heart disease (RIHD) refers to radiation-induced cardiovascular adverse effects caused by thoracic radiotherapy. Currently, there is no uniform standard in the treatment of RIHD. Methods. In our group study, by administering a dose of 4 Gy radiation, we established a radiation injured cardiomyocyte model and explored the regulatory relationship between tanshinone IIA and p38 MAPK in cardiomyocyte injury. We assessed cell damage and proliferation using clonogenic assay and lactate dehydrogenase (LDH) release assay. The measures of antioxidant activity and oxidative stress were conducted using superoxide dismutase (SOD) and reactive oxygen species (ROS). The apoptosis rate and the relative expression of apoptotic proteins were conducted using flow cytometry and western blot. To assess p38 and p53 expressions and phosphorylation levels, western blot was performed. Results. Experimental results suggested that tanshinone IIA restored cell proliferation in radiation-induced cardiomyocyte injury (∗∗P<0.01), and the level of LDH release decreased (∗P<0.05). Meanwhile, tanshinone IIA could decrease the ROS generation induced by radiation (∗∗P<0.01) and upregulate the SOD level (∗∗P<0.01). Again, tanshinone IIA reduced radiation-induced cardiomyocyte apoptosis (∗∗P<0.01). Finally, tanshinone IIA downregulated radiation-induced p38/p53 overexpression (∗∗∗P<0.001). Conclusions. The treatment effects of tanshinone IIA against radiation-induced myocardial injury may be through the regulation of the p38/p53 pathway.